2016
DOI: 10.1097/shk.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Administration Modulates Endothelial Progenitor Cell and Lung Injury in Septic Mice

Abstract: This study investigated the effects of glutamine (GLN) administration on circulating endothelial progenitor cells (EPCs) and lung angiopoietin (Ang) gene expressions in polymicrobial sepsis. Mice were randomly assigned to a normal control group (NC), septic saline group (SS), and septic GLN group (SG). All mice were fed with a chow diet. Sepsis was induced by cecal ligation and puncture (CLP). The mice in SS group were injected with saline, whereas SG group administered 0.75 g GLN/kg body weight once via tail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Mononuclear cells were first identified and CD34 + /CD133 + /CD309 + -cells were gated. Flow cytometric analysis was carried out in accordance to standard settings on a multicolor BD FACS CantoII flow cytometer (BD Biosciences, San Diego, CA, USA), and data were analyzed with BD FACSDiva™ v6.1.3 software (BD Biosciences, San Diego, CA, USA) as described in the previous report [20]. We presented the value of proangiogenic cells in percentage instead of the absolute number among mononuclear cells because the number of proangiogenic cells in plasma are relatively low.…”
Section: Methodsmentioning
confidence: 99%
“…Mononuclear cells were first identified and CD34 + /CD133 + /CD309 + -cells were gated. Flow cytometric analysis was carried out in accordance to standard settings on a multicolor BD FACS CantoII flow cytometer (BD Biosciences, San Diego, CA, USA), and data were analyzed with BD FACSDiva™ v6.1.3 software (BD Biosciences, San Diego, CA, USA) as described in the previous report [20]. We presented the value of proangiogenic cells in percentage instead of the absolute number among mononuclear cells because the number of proangiogenic cells in plasma are relatively low.…”
Section: Methodsmentioning
confidence: 99%
“…It is considered critical for the differentiation, proliferation, and survival in various types of stem cells [16,17]. Previous studies carried out by our laboratory showed that GLN supplementation promotes EPC mobilization in sepsis [18] and in diabetic mice with limb ischemia [19]. Although obesity also exerts inflammation and oxidative stress in the body, the metabolic alterations are distinct from sepsis and diabetes.…”
Section: Introductionmentioning
confidence: 98%
“…Finally, in an article that combines some of the themes investigated by other scientists in this issue (sepsis, ARDS and a single injection of nutritional compound), Dr. Yeh and colleagues have eloquently demonstrated that glutamine can modify progenitor cell and lung injury in mice exposed to severe infection (20). Their basic science work revealed that an intravenous injection of glutamine after cecal ligation and puncture could promote the mobilization of endothelial progenitor cells, in part due to the release of C-X-C motif chemokine 1, vascular endothelial growth factor and nitric oxide (20).…”
mentioning
confidence: 99%
“…Their basic science work revealed that an intravenous injection of glutamine after cecal ligation and puncture could promote the mobilization of endothelial progenitor cells, in part due to the release of C-X-C motif chemokine 1, vascular endothelial growth factor and nitric oxide (20). These effects are associated with improved vascular function, ameliorated inflammation and reduced damage of lung tissues (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation